Comparative Antifungal Efficacy of Cinnamon (Cinnamomum burmannii) and Turmeric (Curcuma longa) Extracts Against Postharvest Anthracnose of Papaya - Titik Nur Aeny; Hasriadi Mat Akin; Selvi Helina; Zakiatun Nafsiyah; Fauziah Rizky Nurfadillah (Agro Bali : Agricultural Journal, 2026)
Anthracnose is a major postharvest disease that reduces the quality and marketability of papaya fruits. This study evaluated and compared the antifungal activity of cinnamon (Cinnamomum burmannii) leaf extract and turmeric (Curcuma longa) rhizome extract against Colletotrichum brevisporum under in vitro and in vivo conditions. The experiment was arranged in a Completely Randomized Design (CRD) consisting of ten treatments with four replicates. Treatments included cinnamon and turmeric extracts at concentrations ranging from 0.25% to 1.00%, a propineb fungicide treatment, and an untreated control. Both extracts significantly inhibited mycelial growth, suppressed conidial germination, and reduced disease development compared with the untreated control (p < 0.05). Turmeric extract consistently exhibited greater antifungal activity than cinnamon extract. At a concentration of 1.00%, turmeric extract reduced colony diameter by 46.84%, decreased disease severity at 6 days after inoculation by 34.6%, and completely inhibited conidial germination compared with the untreated control. Its performance also approached that of propineb during the early stages of infection. However, this study evaluated crude extracts under controlled laboratory and postharvest conditions without phytochemical characterization or validation under commercial storage systems. These findings suggest that turmeric rhizome extract is a promising candidate for further development as an environmentally friendly component of integrated postharvest management of papaya anthracnose, although additional studies on phytochemical composition, formulation, and commercial-scale validation are required before practical application.